The new generation synthetic reconstituted surfactant CHF5633 suppresses LPS-induced cytokine responses in human neonatal monocytes. (October 2016) - Glaser, Kirsten; Fehrholz, Markus; Papsdorf, Michael; Curstedt, Tore; Kunzmann, Steffen; Speer, Christian P.
Abstract: Background: New generation synthetic surfactants represent a promising alternative in the treatment of respiratory distress syndrome in preterm infants. CHF5633, a new generation reconstituted agent, has demonstrated biophysical effectiveness in vitro and in vivo . In accordance to several well-known surfactant preparations, we recently demonstrated anti-inflammatory effects on LPS-induced cytokine responses in human adult monocytes. The present study addressed pro- and anti-inflammatory effects of CHF5633 in human cord blood monocytes. Methods: Purified neonatal CD14 + cells, either native or simultaneously stimulated with E . coli LPS, were exposed to CHF5633. TNF-α, IL-1β, IL-8 and IL-10 as well as TLR2 and TLR4 expression were analyzed by means of real-time quantitative PCR and flow cytometry. Results: CHF5633 did not induce pro-inflammation in native human neonatal monocytes and did not aggravate LPS-induced cytokine responses. Exposure to CHF5633 led to a significant decrease in LPS-induced intracellular TNF-α protein expression, and significantly suppressed LPS-induced mRNA and intracellular protein expression of IL-1β. CHF5633 incubation did not affect cell viability, indicating that the suppressive activity was not due to toxic effects on neonatal monocytes. LPS-induced IL-8, IL-10, TLR2 and TLR4 expression were unaffected. Conclusion: Our data confirm that CHF5633 does not exert unintended pro-apoptotic and pro-inflammatory effects in human neonatal monocytes. CHF5633 rather suppressed LPS-induced TNF-α and IL-1β cytokine responses. Our data add to previous work and may indicate anti-inflammatory features of CHF5633 on LPS-induced monocyte cytokine responses.